A Zinc-Dependent Protease AMZ-tk from a Thermophilic Archaeon is a New Member of the Archaemetzincin Protein Family - Jia, Baolei; Li, Zhengqun; Liu, Jinliang; Sun, Ying; Jia, Xiaomeng; Xuan, Yuan Hu; Zhang, Jiayan; Jeon, Che Ok (Frontiers in Microbiology, 2015)
A putative zinc-dependent protease (TK0512) in Thermococcus kodakarensis KOD1 shares a conserved motif with archaemetzincins, which are metalloproteases found in archaea, bacteria, and eukarya. Phylogenetic and sequence analyses showed that TK0512 and its homologues in Thermococcaceae represent new members in the archaemetzincins family, which we named AMZ-tk. We further confirmed its proteolytic activity biochemically by overexpression of the recombinant AMZ-tk in E. coli and characterization of the purified enzyme. In the presence of zinc, the purified enzyme degraded casein, while adding EDTA strongly inhibited the enzyme activity. AMZ-tk also exhibited self-cleavage activity that required Zn2+. These results demonstrated that AMZ-tk is a zinc-dependent protease within the archaemetzincin family. The enzyme displayed activity at alkaline pHs ranging from 7.0-10.0, with the optimal pH being 8.0. The optimum temperature for the catalytic activity of AMZ-tk was 55ºC. Quantitative reverse transcription-PCR revealed that transcription of AMZ-tk was also up-regulated after exposing the cells to 55 ºC and 65ºC. Mutant analysis suggests that Zn2+ binding histidine and catalytic glutamate plays key roles in proteolysis. AMZ-tk was thermostable on incubation for 4 h at 70°C in the presence of EDTA. AMZ-tk also retained >50% of its original activity in the presence of both laboratory surfactants and commercial laundry detergents. AMZ-tk further showed antibacterial activity against several bacteria. Therefore, AMZ-tk is of considerable interest for many purposes in view of its activity at alkaline pH, detergents, and thermostability.